Perilaku Masyarakat Terhadap Benda Cagar Budaya Sangiran: Studi Kasus Di Desa Krikilan - Bambang Soelistyanto (Balai Arkeologi Yogyakarta, 1995)
Sangiran site in the world of science, especially in the issue of early human evolution is important, there is no doubt. Findings ranging from the right lower jaw (mandible) found by Von Koenigsvald in 1934 to Sugimin's pithecantrophus skull found on October 8, 1993, present evidence that the Sangiran dome is the world's happiest hominid site. Unfortunately, most of the human fossil findings at this site do not come from the results of research by researchers. But the findings of local residents whose activities are far from practical have more opportunities than a formal study.